VA health care : long-term care strategic planning and budgeting need improvement : report to the Chairman, Committee on Veterans' Affairs, House of Representatives. (U.S. Govt. Accountability Office, 2009)
GAO examined (1) VA's reporting of planned workload in its 2007 long-term care strategic plan and (2) VA's long-term care spending estimates, including its cost assumptions and workload projections, in VA's fiscal year 2009 budget justification.